2012
DOI: 10.1186/1742-2094-9-52
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of metabotropic glutamate receptor 5, AKT/PI3K Signaling and NF-κB pathway in methamphetamine-mediated increase in IL-6 and IL-8 expression in astrocytes

Abstract: Methamphetamine (MA) is one of the commonly used illicit drugs and the central nervous system toxicity of MA is well documented. The mechanisms contributing to this toxicity have not been fully elucidated. In this study, we investigated the effect of MA on the expression levels of the proinflammatory cytokines/chemokines, IL-6 and IL-8 in an astrocytic cell line. The IL-6 and IL-8 RNA levels were found to increase by 4.6 ± 0.2 fold and 3.5 ± 0.2 fold, respectively, after exposure to MA for three days. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
117
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(127 citation statements)
references
References 55 publications
9
117
1
Order By: Relevance
“…The nuclear factor-ĸB (NF-κB) signaling is the major pathway that regulates the inflammatory cytokine expression and has been widely studied in inflammatory responses (Kawai and Akira, 2007). Previous studies have reported several stimuli such as lipopolysaccharide (LPS) and METH-induced inflammation in both neuronal cells and glial cells by the overactivation of NF-κB signaling (Flora et al, 2003;Shah et al, 2012;Wires et al, 2012;Perpoonpattana et al, 2013;Coelho-Santos et al, 2015;Jumnongprakhon et al, 2015). Therefore, the inhibition of these negative effects may be beneficial in protecting BBB impairment.…”
Section: Introductionmentioning
confidence: 98%
“…The nuclear factor-ĸB (NF-κB) signaling is the major pathway that regulates the inflammatory cytokine expression and has been widely studied in inflammatory responses (Kawai and Akira, 2007). Previous studies have reported several stimuli such as lipopolysaccharide (LPS) and METH-induced inflammation in both neuronal cells and glial cells by the overactivation of NF-κB signaling (Flora et al, 2003;Shah et al, 2012;Wires et al, 2012;Perpoonpattana et al, 2013;Coelho-Santos et al, 2015;Jumnongprakhon et al, 2015). Therefore, the inhibition of these negative effects may be beneficial in protecting BBB impairment.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have reported several stimuli such as lipopolysaccharide (LPS) and METHinduced inflammation in both neuronal cells and glial cells by the overactivation of NF-κB signaling (Flora et al, 2003;Shah et al, 2012;Wires et al, 2012;Permpoonpattana et al, 2013;Coelho-Santos et al, 2015;Jumnongprakhon et al, 2015). Therefore, the inhibition of these negative effects may be beneficial in protecting BBB impairment.…”
Section: Introductionmentioning
confidence: 93%
“…The authors further showed that repeated administration of IL-6 sensitizes rats to the locomotor-stimulating effects of amphetamine, further suggesting a close interaction between IL-6 and the mesolimbic dopaminergic system (50). Furthermore, in an astrocytic cell line, both acute and chronic exposure to methamphetamine increased IL-6 mRNA and protein levels (51). …”
Section: Cytokines and The Dopamine And Glutamate Hypotheses Of Schizmentioning
confidence: 99%